Various Forms of Tissue Damage and Danger Signals Following Hematopoietic Stem-Cell Transplantation - Ramadan, Abdulraouf; Paczesny, Sophie (Frontiers in Immunology, 2015)
Hematopoietic stem cell transplantation (HSCT) is the most potent curative therapy for many malignant and non-malignant disorders. Unfortunately, a major complication of HSCT is graft-versus-host disease (GVHD), which is mediated by tissue damage resulting from the conditioning regimens before the transplantation and the alloreaction of dual immune components (activated donor T cells and recipient’s antigen-presenting cells). This tissue damage leads to the release of alarmins and the triggering of pathogen-recognition receptors that activate the innate immune system and subsequently the adaptive immune system. Alarmins, which are of endogenous origin, together with the exogenous pathogen-associated molecular patterns (PAMPs) elicit similar responses of danger signals and represent the group of damage-associated molecular patterns (DAMPs). Effector cells of innate and adaptive immunity that are activated by PAMPs or alarmins can secrete other alarmins and amplify the immune responses. These complex interactions and loops between alarmins and PAMPs are particularly potent at inducing and then aggravating the GVHD reaction. In this review, we highlight the role of these tissue damaging molecules and their signaling pathways. Interestingly, some DAMPs and PAMPs are organ specific and GVHD-induced and have been shown to be interesting biomarkers. Some of these molecules even represent potential targets for novel therapeutic approaches.